Evidence of sexual dimorphism in relationships between estrogen receptor polymorphisms and bone mass: the Hertfordshire study. - Dennison, E; Syddall, H; Fall, C; Brandi, M; Cooper, C (2005)
OBJECTIVE: To examine the relationship between estrogen receptor (ER) a and ss gene polymorphisms and bone mass. METHODS: Bone mineral density (BMD) was measured at the lumbar spine and proximal femur twice, 4 years apart, in a cohort of 147 men and 125 women aged 61-73 years. Genomic DNA was extracted from whole blood samples, and genotyping for the ER (PvuII, XbaI, and AluI) was undertaken. RESULTS: There were no significant associations between either the XbaI or PvuII polymorphisms and bone mass, or bone loss in the cohort as a whole. However, men homozygous for the aa beta receptor polymorphism had higher BMD at the lumbar spine (p = 0.05), femoral neck (p = 0.01), and total femur (p = 0.01). Women homozygous for aa had lower femoral neck and total femoral BMD than women of the AA or Aa genotypes (p = 0.01 and p = 0.02). Gender*ERbeta interaction terms were statistically significant (p = 0.02 for lumbar spine BMD, p = 0.0004 for femoral neck BMD, and p = 0.0003 for total femoral BMD, each test with 2 degrees of freedom unadjusted). Adjustment for sex hormone concentration and lifestyle factors made little difference to our results. CONCLUSION: We found relationships between the ERbeta gene and the determination of bone mass among men and women in their seventh decade.